DINAMIKA TRANSPARANSI DAN AKUNTABILITAS KEUANGAN PUBLIK: STUDI KASUS PADA BADAN NARKOTIKA NASIONAL KABUPATEN SUMBAWA - Meilani Al Rahmatia; Sriyatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the dynamics of public financial transparency and accountability at the National Narcotics Agency (BNN) of Sumbawa Regency from the perspective of good governance and agency theory. A qualitative approach with case study method was applied. Data were collected through in-depth interviews, observation, and documentation with the Expenditure Treasurer and the Revenue Treasurer of BNN Sumbawa Regency, then analyzed using the Miles and Huberman interactive model. The results show that financial transparency and accountability at BNN Sumbawa Regency have generally been implemented properly. Transparency is realized through periodic financial reporting and the use of digital systems such as SAKTI, SIMPONI, and CMS, while accountability is reflected in the preparation of accountability reports based on Government Accounting Standards (SAP) and state financial regulations. Supporting factors include human resource competence, internal control systems, and digitalization, whereas network disruptions, system errors, and regulatory complexity remain the main obstacles. The study concludes that the implementation of transparency and accountability at BNN Sumbawa Regency has supported the principles of good governance, although improvements in public information disclosure are still needed to strengthen community participation and trust in public financial management.